Design and Control of a Novel Grip Amplifier to Support Pinch Grip with a Minimal Soft Hand Exoskeleton - Sanders, Quentin; Okita, Shusuke; Lobo-Prat, Joan; De Lucena, Diogo Schwerz; Smith, Brendan W.; Reinkensmeyer, David J. (Proceedings of the ... IEEE/RAS-EMBS International Conference on Biomedical Robotics and Biomechatronics, 2018)
Hand exoskeletons could potentially improve hand use after stroke but are typically obtrusive and non-intuitive. Here, we provide a rationale for a control strategy suitable for a minimalistic hand exoskeleton. We also report on pilot testing of the strategy, and on a soft actuator design for implementing the strategy. The strategy is based on four experimental observations from studies conducted in our laboratory with unimpaired individuals and stroke survivors. First, using only a pinch grip, unimpaired people can achieve a substantial level of hand function when measured with clinical assessments. Second, the level of achieved function corresponds well with what is necessary to drive daily hand use, as measured by a novel wearable sensor with stroke survivors. Third, even people with severe hand impairment after stroke have a well-preserved ability to control isometric finger flexion force, even though they cannot use their hand to manipulate objects. Fourth, such individuals also exhibit highly correlated forces between fingers. From these observations we propose a control strategy that measures residual finger flexion of digits 3-5 (middle-pinky fingers) to control the force of an exoskeleton assisting in pinch grip. We implemented this "residual force control" strategy using the FINGER exoskeleton and found that unimpaired subjects could intuitively use this strategy to pick up an object and learn to amplify their grip force (Repeated Measures ANOVA, p \pmb{< 004} ). We have also begun developing a soft exoskeleton to implement the residual force control strategy, and we report on the actuator design here. The results of preliminary testing of the actuator show that the actuator could produce a sufficient amount of force ( \pmb{13.06} N\pmb{±.33} SD) to assist the hand.